The Influence Of Teamwork And Work Discipline On Employees Performance Of PT. Campina Ice Cream Industry Tbk (Survey on Employees of PT. Campina Ice Cream Industry Tbk Cikoneng) - Fauziyyah, Aulia Nurul; Rahwana, Kusuma Agdhi; Patimah, Titin (Jurnal Multidisiplin, 2024)
This study aims to determine the Effect of Teamwork and Work Discipline on Employees Performance of Campina Ice Cream Industry in Cikoneng, Ciamis. This study uses a descrivtive method with a quantitative approach. The research population was employees of the Campina Ice Cream Industry and used a saturated sampling technique, where all members of the population were sampled, namely 40 people for respondents. Data collection techniques using interviews and questionnaires.The method used is multiole linear regression analysis with SPSS version 25. The results of this study indicate that Teamwork (X1) and Work Discipline (X2) simultaneously have a significant effect on the dependent variable, namely Employees Performance (Y). Teamwork (X1) partially has a positive and significant effect on Employees Performace (Y). Work Discipline (X2) partially has a positive and significant effect on Employees Performance (Y).